Korespondencja Janusza Warmińskiego i Kazimierza Dejmka - Aneta Kielak-Dudzik, oprac. (Pamiętnik Teatralny, 2017)
A selection of letters exchanged between Janusz Warmiński and Kazimierz Dejmek. Both belonged to the generation of Polish theatre directors who started out their careers after the Second World War had ended. They first met in Łódź, where, along with the Grupa Młodych Aktorów [the Group of Young Actors], they founded the Nowy State Theatre, a paragon of the stage meeting the requirements of the doctrine of Socialist Realism. One would expect that Janusz Warmiński and Kazimierz Dejmek went their separate ways in 1952, when the former became head of the Ateneum Theatre in Warsaw whereas Dejmek stayed in Łódź. It would, however, be an overstatement because, as the correspondence published here testifies, they stayed friends and kept in touch for all the years when each worked toward their own vision of theatre, and they could count on each other’s help even at the most critical junctures of their careers. The correspondence presented here is a selection of letters exchanged between Warmiński and Dejmek in 1959–1976. The letters, especially the ones from 1964 and from the turn of the 1960s and 1970s, bring many revelations. Warmiński wrote to Dejmek from the USA, where he lectured at the University of Kansas, Kansas City, and Dejmek wrote to Warmiński when he travelled around Europe after he left Poland at the end of the 1960s. The correspondence focuses mostly on artistic matters. It documents creative puzzles and doubts that both of these great directors faced on a day-to-day basis. It is also very informative when it comes to the social and political circumstances of the theatre life in Poland after the Second World War. The letters published in this issue of Pamiętnik Teatralny are an important and very much needed source of biographical information about both artists. The letters by Warmiński to Dejmek are from the collection of the Zbigniew Raszewski Theatre Institute in Warsaw; the letters by Dejmek to Warmiński come from the archive of the Stefan Jaracz Ateneum Theatre in Warsaw.